2019
DOI: 10.1016/j.archoralbio.2018.10.037
|View full text |Cite|
|
Sign up to set email alerts
|

MMP-3 and MMP-8 in rat mandibular condylar cartilage associated with dietary loading, estrogen level, and aging

Abstract: Objectives: The structure of the mandibular condylar cartilage (MCC) is regulated by dynamic and multifactorial processes. The aim of this study was to examine the effects of altered dietary loading, estrogen level, and aging on the structure of the condylar cartilage and the expressions of matrix metalloproteinase (MMP) -3 and MMP-8 of rat MCC.Methods: In this study, Crl:CD (SD) female rats were randomly divided into 3 groups according to dietary hardness: hard diet (diet board), normal diet (pellet), and sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Studies have confirmed that MMP-3 is the most important hydrolase, which has a strong ability to activate various MMP precursors, gelatinase, and collagenase to degrade the extracellular matrix of cartilage and bone [30], and its increasing level is positively correlated with the degree of cartilage destruction [31,32]. In our study, LIPUS effectively reduced MMP-3 expression levels in damaged condylar cartilage caused by CSD treatment.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Studies have confirmed that MMP-3 is the most important hydrolase, which has a strong ability to activate various MMP precursors, gelatinase, and collagenase to degrade the extracellular matrix of cartilage and bone [30], and its increasing level is positively correlated with the degree of cartilage destruction [31,32]. In our study, LIPUS effectively reduced MMP-3 expression levels in damaged condylar cartilage caused by CSD treatment.…”
Section: Discussionsupporting
confidence: 73%
“…The LIPUS 30, 45, and 60 group rats received the LIPUS intervention at the corresponding intensity for 20 min daily [15] under isoflurane gas anesthesia while simultaneously undergoing CSD. The bilateral temporomandibular joint intervention was performed using the OSTEOTRON IV ultrasound equipment (Ito Ultrawave Co., Ltd., Tokyo, Japan), the ultrasound intensity of which includes three levels (30,45, and 60 mW/cm 2 ): the ultrasound frequency was 1.0 MHz, the pulse width was 200 μs, and the repetition rate was 1 kHz.…”
Section: Csd and Lipusmentioning
confidence: 99%
“…The thickness of MCC has been demonstrated to be relied on the mechanical loading, which had a great effect on proliferation. 15 - 17 Compared with the normal diet group, MCC harvested from the soft diet group was thinner. The significant difference was mainly found in anterior and posterior part of MCC, which is similar to Rusu et al’s 18 findings.…”
Section: Discussionmentioning
confidence: 97%
“…The anterior part of MCC was suggested to be sensitive to mechanical loading. 17 , 19 Even though the thickness of middle part was growing, we considered that the stress sensibility of middle part was not as strong as the other two parts, because of the smaller number of BrdU-positive cells.…”
Section: Discussionmentioning
confidence: 99%
“…Various biomarkers of aging/disease have been associated with biological functions ( Supplementary Table S5 ). For example, MMP8, the top aging marker, is a collagenase with proteolytic activity against matrix proteins and is an important participant in the function of the vascular system and the development of atherosclerosis ( Laxton et al, 2009 ; Toba et al, 2017 ; Yu et al, 2019 ). Its expression in the heart increases with chronological age, enabling it to regulate signal transduction during the aging process by regulating the expression and activity of cytokines, chemokines, growth factors, hormones, and angiogenic factors ( Mota et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%